Manipuri Film Industry - Singh, M Bimolchandra (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In this article, researcher critically analyzes the multiple challenges faced by Manipuri film industry. Manipuri film industry, even though a very small film industry it is, has been obviously giving a big contribution to the Indian film Industry, and even to the international scenario since 1972 with the production of its first feature film ‘Matamgi Manipur’. The State bagged 57 National Film Awards - 27 for feature films and 30 for non-feature (Short and Documentary) films till 2014. Unfortunately, for the last two decades, Manipuri film industry has been diminishing its prestige of making international and national acclaimed films. Hence, the researcher is very much curious to critically analyze the challenges faced by Manipuri film industry. For this study, researcher conducted a telephonic interview with a senior Manipuri film journalist of The Poknapham, a Daily Manipuri Newspaper which has the largest circulation in Manipur and also used the official documents published by Directorate of Film Festival, Ministry of Information and Broadcasting, Government of India. How to cite this article: Singh MB. Manipuri Film Industry. J Adv Res Jour Mass Comm 2018; 5(1&2): 25-30. DOI: https://doi.org/10.24321/2395.3810.201805